2011
DOI: 10.1159/000330285
|View full text |Cite
|
Sign up to set email alerts
|

Improved Automated Screening of Diabetic Retinopathy

Abstract: Aim: To assess a two-step automated system (RetmarkerSR) that analyzes retinal photographs to detect diabetic retinopathy for the purpose of reducing the burden of manual grading. Methods: Anonymous images from 5,386 patients screened in 2007 were obtained from a nonmydriatic diabetic retinopathy screening program in Portugal and graded by an experienced ophthalmologist. RetmarkerSR earmarked microaneurysms, generating two outputs: ‘disease’ or ‘no disease’. A second-step analysis, based on coregistration, com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 35 publications
0
52
0
5
Order By: Relevance
“…38 One study showed that Retmarker can detect referable retinopathy with a sensitivity of 95.8% and a specificity of 63.2%. 39 Retmarker can also perform predictive longitudinal analysis using microaneurysm turnover. Two independent prospective longitudinal studies using the Retmarker on single-field images have demonstrated the relationship of increased microaneurysm turnover rates identified by the Retmarker program and an increased rate for developing clinically significant macular oedema.…”
Section: Idx-drmentioning
confidence: 99%
See 1 more Smart Citation
“…38 One study showed that Retmarker can detect referable retinopathy with a sensitivity of 95.8% and a specificity of 63.2%. 39 Retmarker can also perform predictive longitudinal analysis using microaneurysm turnover. Two independent prospective longitudinal studies using the Retmarker on single-field images have demonstrated the relationship of increased microaneurysm turnover rates identified by the Retmarker program and an increased rate for developing clinically significant macular oedema.…”
Section: Idx-drmentioning
confidence: 99%
“…EyeArt and Retmarker in this study produced similar sensitivity to that previously reported on different data sets. 39,42 Health economics comparison with previous literature A number of previous studies have examined the cost-effectiveness of diabetic retinopathy screening (e.g. James et al, 62 Javitt et al…”
Section: Sensitivity and Specificitymentioning
confidence: 99%
“…Moreover, it includes a proprietary coregistration algorithm that allows comparison within the same retinal location between different screening visits for the same eye [20]. …”
Section: Methodsmentioning
confidence: 99%
“…These programs involve a considerable amount of data to be analyzed by trained readers/graders or by reading centers. With the purpose of reducing the human burden in relation to the grading of the screening images, a number of automated systems allowing classification of images as having/not having lesions of DR have been proposed [18,19,20,21,22]. …”
Section: Introductionmentioning
confidence: 99%
“…The system was later extended to detect changes in vasculature width and appearance/disappearance of lesions [26]. A commercial system also exists for automatically detecting temporal retinal changes due to red-dot-like lesions from a pair of fundus images of the same retina [27], [28].…”
Section: Introductionmentioning
confidence: 99%